Post-urethroplasty complications in hypospadias repair: a systematic review and meta-analysis comparing polydioxanone and polyglactin sutures - C K Sinha; Tridip Dutta Baruah; Nitinkumar Borkar; Charu Tiwari; Debajyoti Mohanty; Manoj Mohanty (BMJ Publishing Group, 2024)
Background Polyglactin (PG) and polydioxanone (PDS) sutures are extensively used based on the surgeon's preference. The development of post-reconstruction urethrocutaneous fistula (UCF) is variably attributed to the choice of suture material for urethroplasty. This meta-analysis compares complications of hypospadias repair using PG and PDS sutures.Methods The systematic review and meta-analysis were performed as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The authors conducted thorough searches in databases including MEDLINE, EMBASE, CENTRAL, Scopus, Google Scholar, and clinical trial registries. Outcome measures included UCF, meatal stenosis, wound infection, urethral stricture, glans dehiscence, and overall complications. Quantitative analysis was used with fixed or random-effect models to find the pooled risk ratio and I2 heterogeneity.Results The criteria for inclusion were met by five comparative studies with the inclusion of 1244 children altogether. Pooled analysis failed to show a statistically significant difference in the incidence of meatal stenosis, urethral stricture, wound infection, and total complications using PG and PDS sutures. However, it showed a reduction in the incidence of UCF with PDS suture hypospadias repairs (risk ratio=0.66, 95% CI 0.48 to 0.92).Conclusions PDS sutures are associated with decreased incidence of UCF than PG after hypospadias repair. The incidence of meatal stenosis, urethral stricture, wound infection, and total complications was not affected by the type of suture material used for repair.Clinical implications This meta-analysis suggests decreased incidence of UCF when PDS sutures are used for hypospadias repair which may impact the choice of suture material for repair.PROSPERO registration number CRD42023409710.